The Analysis of Social-emotional Development of Low-class Students in Learning - Johannes, Nathalia Y.; Mahananingtyas, Elsinora; Kapelle, Noky R.; Pasalbessy, Chyntia (KnE Social Sciences, 2024)
This study aimed to determine the social-emotional development of low-class students in learning. This study employed a descriptive qualitative approach used to use facts, and the study also focused on analysing the social-emotional development of low-class students at SD Negeri 92 Central Maluku. This study had a total of 30 student participants. Data collection was done by observation, documentation, and interviews with class teachers. The data analysis technique used is descriptive statistical analysis. The instrument was assessed by the observer using a Likert scale, with a score of 1-4, the highest score for each item was 4 (often) and the lowest was 1 (never). The results of the study showed that students’ social-emotional development in learning was good, and this can be seen from the aspects of students’ self-awareness which obtained an average result of 3.23 in the good category, the responsibility aspect obtained an average result of 2.77 in the good category, and the relationship skill aspect obtained an average result of 3.01 in the good category. Keywords: social-emotional, low-class students, learning